The Alliance for Recovery Research in Music Therapy: Developing a Shared Research Agenda in Mental Health - McCaffrey, Tríona; Carr, Catherine E.; Solli, Hans Petter Paulen; Bent, Cornelia; Boyle, Darmuid; Dypvik, Oda Bjørke; Dybdahl, Kenneth; Hayes, Tommy; Hickling, Lauren M.; Fernandez, Jane; et al. (Voices: A World Forum for Music Therapy, 2024)
The mental health recovery movement recognises the importance of expertise by experience held by service users alongside healthcare practitioners. Recovery has gained attention in music therapy but a situation prevails where practitioners and researchers set research agendas. A group of music therapists recognised the absence of service user voices in music therapy research, and in 2017 they established a network called the Alliance for Recovery Research in Music Therapy (ARRIMT). In 2020, they started to develop a multi-national platform to explore mental health recovery in relation to research. Service users and music therapists were invited from three countries including Ireland, Norway, and the United Kingdom (UK). Local meetings were held to introduce stakeholders from each country, followed by three online meetings. Music was central to each meeting and each built upon content from previous meetings. Our conversations opened up new possibilities for working together. Four priorities for practice and research were identified: Music as a connector; music between sessions; music technology; and, online music therapy. This report will share our process and what we learnt from working together. We contextualise our work within concepts of foregrounding and mattering and view this work as a crucial step towards meaningful co-production. We reflect upon the role of music in building group identity alongside the importance of careful curation. Finally, we present ideas for future music therapy and mental health research. Group Description In 2018 the Alliance for Recovery Research in Music Therapy (ARRIMT) was founded as an international group of music therapy service users, researchers and practitioners from Australia, Ireland, Norway, and the United Kingdom. Fundamental to this group is the concept of recovery where those who use and those who provide mental health services work together to share knowledge and experiences that can have a positive impact on mental health service delivery. Key to this is listening carefully to the voices of those who use music therapy so that their views and experiences influence how music therapy is offered in mental health services. The founders and coordinators of the group are Tríona McCaffrey, Hans Petter Paulen Solli, and Catherine E. Carr. Other members of the group are Cornelia Bent, Darmuid Boyle, Oda Bjørke Dypvik, Kenneth Dybdahl, Tommy Hayes, Lauren M. Hickling, Jane Fernandez, Anne Malerbakken, Brendan Ruddy, and Torgrim Vågan.